PENGARUH LABEL HALAL DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK - Zaenal, Rini Susilawati; Sukmarani, Wendri (Sekolah Tinggi Ilmu Ekonomi SBI, 2024)
The goal of this research is to determine the influence of the halal label on cosmetic purchasing decisions within the STIE Nusa Megarkencana Yogyakarta employee environment. This research variable uses three variables, namely two independent variables, namely; Halal Label (X1) and Product Quality (X2) and Purchasing Decisions as independent variables (Y). The population in this research is STIENUS students, especially the class of 2023/2024 as consumers who buy halal certified cosmetic products. The sampling technique used purposive sampling and a research sample of 50 respondents was obtained. The method used is a quantitative research method. Based on the results of this research, the Halal Label and Product Quality variables are the variables that have a dominant influence on the cosmetic purchase decision variable for consumers at STIE Nusa Megarkencana Yogyakarta. It is proven by the descriptive results that halal labels have a significant influence on purchasing decisions. From the results of the F test it can be concluded that there is a simultaneous and significant influence of the halal label and product quality on purchasing decisions. The results obtained were a coefficient of determination or (R2) of 18%. This means that 18% of the variation in changes in the ups and downs of purchasing decisions is due to the halal label variable. and product quality, while the remaining 82% is caused by other factors not analyzed in this research Keywords: halal, product quality, purchasing decisions